KAITAN ASUPAN VITAMIN A DENGAN PRODUKSI AIR SUSU IBU (ASI) PADA IBU NIFAS - Bibi Ahmad Chahyanto; Katrin Roosita (Jurnal Gizi dan Pangan, 2013)
This study aimed to analyze association between intake of vitamin A with breast milk production of postpartum mothers. A cross sectional study of 30 postpartum mothers was conducted in Ciherang, Sukawening, Dramaga, Sinarsari, and Neglasari Villages, Subdistrict of Dramaga, District of Bogor, during April to May 2013. Vitamin A intake of postpartum mothers from food source of vitamin A was 565±351.40 RE while sufficiency level of vitamin A was 66.50±41.30%. Most of postpartum mothers perceived that their breast milk production for infants were fulfilled (80%). The results showed that vitamin A intake was significantly associated with breast milk production (p<0.05). As intake of vitamin A in postpartum mothers increased, breast milk production for infants would be fulfilled.